Questioning the Leadership and Preferences of Regional Heads in Determining Minimum Wage - Harahap, Hadry; Hamid , Adnan (International Journal of Scientific Research and Management (IJSRM), 2020)
This study aims to identify and questioning  the leadership and preferences of regional heads in setting minimum wage policies. The research method used is normative juridical legal research, using a statutory approach in the national labor law system. The results showed that the regional head has the authority to set the minimum wage for workers / laborers to meet the needs of a decent life (KHL) by determining the UMSP and UMSK. As public leaders, regional heads are expected to have transformational leadership behavior, be able to present the vision, mission, and task completion plans as well as problem solvers, produce a positive work environment to strengthen professionalism, transparency in decision making, and trust. Then the regional head is expected to be able to make innovative efforts related to human resource development, creative industry development and programs that support small and medium enterprises so that they can be an option in overcoming labor problems.